Efektivitas Dewan Komisaris dalam Memoderasi Hubungan Financial Distress dan Ukuran Perusahaan Terhadap Manajemen Laba - Triva Maria Manik; Yohanes Adi Nugroho; Andika Patria (Politeknik Ganesha Medan, 2026)
The aim of this study is to show the impact of financial difficulties and bussines scale on profit management, by including measurements on the commission’s board as a moderation variable. Abuse in financial reporting that occurs in several companies is the background for the significance of this research, from the context of corporate transparency and accountability in Indonesia. This research was conducted in the food and drink industry for the period 2022–2024 listed on the IDX. There were 95 populations and 105 selected samples. This study uses Eviews 12 and Moderated Regression Analysis (MRA) software. Analysis of data was performed using regression analysis of panel data utilizing a common effect model (CEM) approach. The research results indicated that financial difficulties, firm size, and commissioners’ board lacked a major impact on profit control method. Furthermore, the size of commissioners’ board has also been shown not to play a role as a moderator on financial difficulties and the company size towards profit management. These findings suggest that the quantity of members of the commissioners’ board, the extent of the firm's assets, and financial pressures are not the main determinants in managers' decisions to manipulate profits. The assessment makes an important contribution to strengthening corporate governance standards and accounting practices, along with a source for investors and regulators in assessing aspects that impact the dependability and precision of financial statements.